PERKEMBANGAN DAN PERTUMBUHAN PRODUK OLAHAN BUAH PALA (RUPALA) DI KOTA PEMATANG SIANTAR SEBAGAI PENUNJANG PEREKONOMIAN MASYARAKAT - Dian G. Purba Tambak; Fidia C. Sitorus; Muzfirah Filzah; Elsa D. Naibaho; Parlin Damanik; Jhoni F. Manurung; Fadilah R. M. Siregar (CV. Denasya Smart Publisher, 2024)
Processed nutmeg products that can increase the added value of nutmeg, increase income, and provide benefits for nutmeg farmers and industry. One of the cottage industries on Jln. Melanthon Siregar No.204, Siantar Marimbun District, Pematang Siantar. They develop products by processing nutmeg into sweets, dodol, syrup, nutmeg jam and the seeds are processed into nutmeg spices which have many health benefits. . This observation was carried out at the Rupala industrial house. This study aims to obtain information about the use of nutmeg plants (Myristica fragrans) by the community. This research was conducted by survey methods, data collection techniques by interview, direct observation and observation. The study population is the people of Siantar Marimbun District who have processed nutmeg products. The results of the study found that the most processed or produced nutmeg plant organs by Mr. Harry Harahap were fruits and seeds. With the variety of processed nutmeg, it can be used as a typical souvenir of Siantar.